Practical Model of Infection Prevention and Control in Intensive Care Units for Iran - Salehi, Zahra; Mohammadnejad, Esmaeil; Aliramezani, Amir (International Journal of Medical Science and Clinical Research Studies, 2023)
Background and Objectives: Nosocomial infections, especially in intensive care units as well as increased mortality and costs associated with them are considered as one of the major health problems in the communities so that successful control of them requires awareness on their problems in the hospitals and a precise planning. This study was conducted to "provide a model for prevention and control of nosocomial infections in intensive care units". Methods and Materials: This qualitative study was conducted through purposeful sampling strategy on 21 healthcare providers selected via purposive sampling from various medical subgroups, including: anesthesiologist, nurse manager, supervisors, faculty members, head nurses, and hospital managers. The data were collected using semi-structured interviews and conventional content analysis method was used for data analysis. In the second phase, a comparative study of the situation of our country and targeted countries was conducted and in the third phase a practical model is designed. Results: The results of qualitative content analysis using conventional approach in the field of staff’s experiment regarding the model of prevention and control of nosocomial infections in intensive care units, revealed 3 main themes: "barriers (human factors, environmental factors, personal factors and complexity)", "facilitating factors (organizational, external and internal stimuli) ", and "concepts of the model (effectiveness of infection control training process in ICU, the systematic nature of the process of infection control, public hospital management, resource management and organizational leadership)". After a comparative study, the applied model of control and prevention of nosocomial infection in the ICU was designed with seven models, including standards (caring-curing and structural), monitoring and supervision, education and training, logistic resources, modern technologies, translation and knowledge transfer and evidence-based practice. Conclusion: Identifying the barriers and facilitating factors of nosocomial infection control and the use of especial measures in ICU promote the patient’s safety and enhance the quality of care. Prevention of these infections requires a comprehensive and integrated controlling program. This model can be applied to resolve existing gaps and cause maximum integrity between the concepts.